LAMB WAVE MODE DISPERSION IN COMPOSITE LAMINATES - Pysarenko, Alexander (SWorld-Ger Conference proceedings, 2024)
This study aims to improve the in situ structural health monitoring method to localize the impact source and determine the Lamb flexural mode A0 velocity in composite structures with unknown stacking and cross-section. The algorithm is based on the differ